A Quantitative Analysis of the Main Lithuanian Taxes and their Optimisation during an Economic Crisis - Švabovič, Miroslav; Miškinis, Algirdas (Ekonomika, 2017)
Seeking to contribute to the analysis of anti-crisis economic policy decisions, the authors of the current article have developed an economic analysis modelling system of the main tax rates, which makes it possible to carry out research into modelling economic scenarios in order to determine the variables of optimal tax rates. By applying this modelling system in practice, it is possible to measure the maximum probability rates of Value Added, Profit, and Personal Income Taxes for the collection of necessary revenues to the state budget. This method presents a possibility to accurately evaluate the impact of fiscal policy measures on the state budget as well as to reflect economic processes more comprehensively and model accurate short- and long-term projections.
Keywords: budget revenue; fiscal policy; tax rates; model projections; economic policy